Raised beds, raised profits - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
For farmers in dry areas, it is sometimes hard to keep solvent. George Kasimo, from Kitui district, Eastern Kenya, took his spade and developed his own way of intensive vegetable farming, growing onions, cabbages and tomatoes and selling them on...